Improving Inpatient Unit Performance Through the Malcolm Baldrige Framework: A Study in a Hospital in Gresik, Indonesia - Haksama, Setya; Prayoga, Diansanto; Azhary, Muhammad; Zeinsar, Syahprevi Rayyan; Sriram, Shyamkumar; Al Mamun, Abdullah (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Numerous studies have explored various aspects of performance in healthcare services, including patient satisfaction, staff well-being, and resource capacity. However, research addressing these gaps using the Malcolm Baldrige Performance Criteria framework remains limited. This study aims to evaluate and enhance the inpatient service performance at Mabarrot Gresik Islamic Hospital using the Malcolm Baldrige Performance Criteria model. An analytical observational study with a cross-sectional approach was conducted to analyze the relationships and correlations among eight Malcolm Baldrige criteria: Organizational Profile, Leadership, Strategic Planning, Customer Focus, Measurement, Analysis, and Knowledge Management, Human Resources, Operational Activity Focus, and Results. Data were collected from 34 respondents, comprising medical and non-medical staff, using a validated (CVI = 0.77) and reliable (α = 0.986) questionnaire. The analysis revealed that Human Resources (r = 0.993), Results (r = 0.837), and Strategic Planning (r = 0.758) demonstrated very strong relationships with Customer Focus, indicating these areas significantly impact inpatient service performance. Furthermore, a strong correlation was found between Customer Focus and Results (r = 0.837), emphasizing the importance of prioritizing patient satisfaction to achieve better outcomes. However, the study identified a weak relationship between the Organizational Profile and Measurement, Analysis, and Knowledge Management criteria, indicating a misalignment that requires attention. The findings suggest that improving human resource performance and addressing customer needs are critical strategies for enhancing inpatient services.